Optimalisasi Digital Marketing dan Legalitas Pengembangan Usaha Mikro Kecil dan Menengah (U.M.Km) di Desa Mojowono Kabupaten Mojokerto - Ratih Dwi Pangestu; Ana Indrawati; Wyda Lusiana; Novellita Sicillia Anggraini; Cindy Alisia Artanty; Moh. Kamaluddin; Jaka Prima (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This community service was carried out in Sumbersari Hamlet, Community Service Activities were carried out in Mojowatesrejo Village, Kemlagi District, Mojokerto Regency with the target of understanding Digital Marketing Optimization and the Legality of Micro, Small and Medium Enterprises Development (U.M.K.M). Carrying out community service, the main aim of this activity is to increase insight and knowledge regarding Optimization of Digital Marketing and the Legality of Micro, Small and Medium Enterprises (UMKM) Development in Mojowono Village. In order to obtain and support a conducive working atmosphere, work together to build productive partnerships. Therefore, the socialization carried out in Mojowono Village, Kemlagi District, Mojokerto Regency is very important to carry out. Other objectives include providing an understanding of technological advances that must be utilized properly so that they can increase income in society. This business activity must of course be maximized and must be equipped with a business permit so that it can provide certainty and legal protection for Micro, Small and Medium Enterprises(UMKM)